Contributing Factors for Adult with osteoarthritis in Al Diwaniya Governorate Hospitals - Alaa I. Saied; Hussein H. Atiyah (Kufa Journal for Nursing Sciences)
Objective: To assess of contributing factors for adult with osteoarthritis and to find out the relationship between demographic characteristic with contributing factors for osteoarthritis.